2004
DOI: 10.1128/iai.72.5.2628-2634.2004
|View full text |Cite
|
Sign up to set email alerts
|

Down-Modulation of Lung Immune Responses by Interleukin-10 and Transforming Growth Factor β (TGF-β) and Analysis of TGF-β Receptors I and II in Active Tuberculosis

Abstract: Immune factors influencing progression to active tuberculosis (TB) remain poorly defined. In this study, we investigated the expression of immunoregulatory cytokines and receptors by using lung bronchoalveolar lavage cells obtained from patients with pulmonary TB, patients with other lung diseases (OLD patients), and healthy volunteers (VOL) by using reverse transcriptase PCR, a transforming growth factor ␤ (TGF-␤) bioactivity assay, and an enzyme immunoassay. TB patients were significantly more likely than OL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
114
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(126 citation statements)
references
References 52 publications
9
114
0
1
Order By: Relevance
“…Nevertheless, in our in vitro model, the blocking of IL-10 in the Mtb-derived conditioned media seems to be sufficient to impair STAT3 activation and the establishment of M2-like phenotype. This is in line with the fact that IL-10 is considered to be an important clinical biomarker of disease progression [54], increased levels for this cytokine are reported in both the blood [31,55] and in the bronchoalveolar lavage of active TB patients [56], and in the tuberculous granuloma context in NHP model [57]. The fact that we observed elevated levels of activated STAT3 in monocyte-macrophages in both TB patients and in the NHP tuberculous granuloma context, suggests that overactive production of IL-10 may be responsible.…”
Section: Discussionmentioning
confidence: 53%
“…Nevertheless, in our in vitro model, the blocking of IL-10 in the Mtb-derived conditioned media seems to be sufficient to impair STAT3 activation and the establishment of M2-like phenotype. This is in line with the fact that IL-10 is considered to be an important clinical biomarker of disease progression [54], increased levels for this cytokine are reported in both the blood [31,55] and in the bronchoalveolar lavage of active TB patients [56], and in the tuberculous granuloma context in NHP model [57]. The fact that we observed elevated levels of activated STAT3 in monocyte-macrophages in both TB patients and in the NHP tuberculous granuloma context, suggests that overactive production of IL-10 may be responsible.…”
Section: Discussionmentioning
confidence: 53%
“…9,36 In addition to earlier reports that BAL fluids from a significant number of tested tuberculosis patients contained elevated IL-10 levels and bioactive TGF-b, 7 recent reports showed that lung cells from induced sputum expressed significantly high levels of IL-10, TGF-bRI and TGF-bRII. 37 In the present study, we found that the addition of anti-IL-10 or anti-TGF-b could partially reverse IFN-c production, suggesting that local IL-10 and TGF-b in PF may promote a cytokine microenvironment where resident and newly recruited immune cells become refractory to appropriate activating signals.…”
Section: Pf Inhibits the Functions Of T Cells And Differentiation Ofmentioning
confidence: 92%
“…IL-10 and TGF-b, the two classical regulatory cytokines, are known to not only inhibit T-cell activity in response to Mtb, 7 but also promote T-cell anergy possibly by downregulating the cell surface expression of the costimulatory and antigen-presenting molecules on Mtb-infected monocytes. 9,36 In addition to earlier reports that BAL fluids from a significant number of tested tuberculosis patients contained elevated IL-10 levels and bioactive TGF-b, 7 recent reports showed that lung cells from induced sputum expressed significantly high levels of IL-10, TGF-bRI and TGF-bRII.…”
Section: Pf Inhibits the Functions Of T Cells And Differentiation Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Some intracellular bacteria down-regulate MHC class I or MHC class II surface expression (28 -31). Mycobacterium tuberculosis skews the cytokine response from a pro-to an antiinflammatory response (32,33). Legionella pneumophila causes IFN-␥-stimulated macrophages to produce PGE 2 , and blocks IFN-␥ secretion from CD4 ϩ T cells (34).…”
mentioning
confidence: 99%